A new TaqMan method for the reliable diagnosis of Ehrlichia spp. in canine whole blood - Kirsty Thomson; Tal Yaaran; Alex Belshaw; Lucia Curson; Laurence Tisi; Sarah Maurice; Guy Kiddle (Parasites & Vectors, 2018)
Abstract Background Ehrlichiosis is an important emerging infectious disease of the canid family and humans worldwide. To date, no extensive evaluation or validation of a molecular diagnostic test for ehrlichiosis has been published. Here, we present data for a newly designed TaqMan assay and compare its performance to a commercial technology (PCRun®). Both of these real-time methods of analysis were evaluated using a comprehensive number of prospective and retrospective samples collected from dogs exhibiting symptoms of ehrlichiosis. Results Whole blood samples collected from dogs, retrospectively in the United Kingdom and prospectively in Israel, were analysed for the presence of Ehrlichia canis and Ehrlichia minasensis DNA using the TaqMan PCR, developed specifically for this study. The results were compared to those of a real time commercial isothermal amplification method (PCRun® system developed by Biogal Galed Labs ACS, Galed, Israel). The sensitivity and specificity (CI: 95%) of the TaqMan PCR and PCRun® were both determined to be 100% and absolute, for all of the samples tested. Interestingly, both tests were demonstrated to be highly comparable, irrespective of differences in amplification chemistry or sequences targeted. Host differences, incidence of disease and geographical location of the isolates had little impact on the positivity recorded by each of the diagnostic methods. Conclusions It was evident that both amplification methods were equally suited for diagnosing canine ehrlichiosis and while the PCRun® clearly amplified all clinically relevant Ehrlichia species known to infect dogs and humans, the TaqMan method was more specific for E. canis and E. minasensis. This work demonstrates that despite good analytical sensitivities and specificities for Ehrlichia spp. neither method could fully account for the clinical diagnosis of thrombocytopenia.